"Even Our 2nd Class Cars are More Comfortable Than Motor Buses!": An Analysis of Victorian Railway Posters Between the Wars. Issue 3 (2nd July 2016) - Symes, Colin
ABSTRACT: Railway posters from the 1920s and 1930s are now regarded as one of the high points of twentieth-century graphic art. While their iconographies have been the subject of considerable scholarly analysis, the contexts in which they operated and functioned have received much less attention. This paper, which focuses on posters produced by Victorian Railways for a range of purposes not necessarily travel related, redresses this. It is argued that railways posters, which operated in conjunction with other forms of railway propaganda, provided a convenient and attractive way for the state to operate on its population, at a distance. Hence, they were used as rhetorical devices to exhort Victorians to travel by rail, to eat more fruit and thereby assist the state's primary producers. As competition from motorisation became more intense during the Depression, resulting in pronounced and unsustainable rail deficits, the need to diversify the sources of railway revenue, as the analysed posters reveal, became more exigent.